COMPARATIVE ANALYSIS OF CONSUMER ATTITUDE AND SOCIAL INFLUENCE BETWEEN MALE AND FEMALE OF COUNTERFEIT PRODUCT (CASE STUDY: WAKAI SHOES) - Repi, Christopel Alexander; Massie, James D.D; Rumokoy, Farlane S (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: This research aims to find out if there is significant difference in purchase intention based on consumer attitude and social influence between male and female customers of counterfeit wakai shoes. Counterfeit products have been found to be a serious problem around the world in recent days where counterfeiting is associated with many problems that causes havoc not only in economic activities but also affect social life as well. The international trade of counterfeit product is enormous. Purchasing intention of counterfeit wakai shoes are currently increasing because there are a lot of people who become the buyers of this product. Counterfeit wakai shoes are easy to found because it is sold everywhere. This research conducted by a quantitative method and this research population is the buyers of wakai counterfeit shoes. By using an Independent Sample t-test, this research conducted a hypothesis is significant difference in consumer attitude and social influence between male and female customers of counterfeit wakai shoes. Based on the result of this research, the data is normally distributed and homogenous. The result shows that there are no significant differences in purchase intention based on consumer attitude and social influence between male and female customers of counterfeit wakai shoes. Findings suggest that original manufactures have to make a mark or hologram unable to imitate so there will be a significant differences between original and counterfeit.Keywords: counterfeiting, consumer attitude, social influence, gender.